Case report of Langerhans cell histiocytosis in a fetus detected by magnetic resonance imaging. Issue 1 (4th November 2020) - Bao, Zhongkun; Deng, Meixiang; Zou, Yu; Wang, Hongzhu; Liang, Jiawei; Mi, Yanhong
Abstract: Langerhans cell histiocytosis (LCH) is a rare disease, and the diagnosis of LCH is mainly based on clinical manifestation, imaging and pathological examinations. But during pregnancy, imaging examinations especially play an important role in the diagnosis and prognostic assessment of fetal LCH. Up to now, there has been no report about magnetic resonance imaging (MRI) features of fetal LCH. We reported a 32‐year‐old woman at 36 weeks' gestation took fetal MRI because of fetal anomalies diagnosed by ultrasonography. On the fetus's MR images, the thymus was slightly enlarged with smooth or lobulated contour in supra anterior mediastinum, displayed heterogeneous signals and contained multiple small cysts on T2WI. Innumerable irregular nodules and patchy shadows were present throughout both lungs. Pulmonary lesions were bilateral and diffuse with relative sparing of the costophrenic angles. The margins of these lesions were fluffy and indistinct. These lesions showed heterogeneous signals on T2WI. MRI showed no lesions in skin region. After birth, lots of round or oval skin lesions distributed all over the baby's body presenting as ulcerated or blister‐like rashes. The chest computer tomography (CT) showed punctate calcification and heterogeneous enhancement in the thymus and bilateral diffuse reticular or reticulonodular opacities in both lungs with fluffy and indistinct margins. Pathological finding was consistent with LCH. Through reporting MRI features of LCH in one fetus, this study aims to improve awareness of fetal LCH in radiologists and clinicians, to improve the prenatal diagnostic rate of this disorder.